In-situ wound healing by SDF-1-mimic peptide-loaded click crosslinked hyaluronic acid scaffold - Kim, Young Hun; Kim, Shina; Ju, Hyun Jin; Han, Min Ji; Park, Yongdoo; Kim, Eunha; Choi, Hak Soo; Choi, Sangdun; Kim, Moon Suk (Journal of Controlled Release, 2023)
Endogenous stem cell-based in-situ tissue regeneration has recently gained considerable attention. In this study, we investigated the potential of a chemokine, SDF-1-mimic peptide (SMP), to promote endogenous stem cell-based in-situ wound healing. Our approach involved the development of a click crosslinked hyaluronic acid scaffold loaded with SMP (Cx-HA + SMP) to release SMP in a wound site. The Cx-HA scaffold maintained its structural integrity throughout the wound healing process and also captured endogenous stem cells. Gradual SMP release from the Cx-HA + SMP scaffold established a concentration gradient at the wound site. In animal wound experiments, Cx-HA + SMP exhibited faster wound contraction compared to Cx-HA + SDF-1. Additionally, Cx-HA + SMP resulted in approximately 1.2–1.6 times higher collagen formation compared to Cx-HA + SDF-1. SMP released from the Cx-HA + SMP scaffold promoted endogenous stem cell migration to the wound site 1.5 times more effectively than Cx-HA + SDF-1. Moreover, compared to Cx-HA + SDF-1, Cx-HA + SMP exhibited higher expression of CXCR4 and CD31, as well as the positive markers CD29 and CD44 for endogenous stem cells. The endogenous stem cells that migrated through Cx-HA + SMP regenerated into wound skin with minimal scar granule formation, similar to the normal tissue. In conclusion, SMP peptide offers greater convenience, while efficiently attracting migrating endogenous stem cells compared to the SDF protein. Our findings suggest that Cx-HA + SMP scaffolds hold promise as a strategy to enhance endogenous stem cell-based in-situ wound healing.
Keywords: Cell-based; Chemokines; Crosslinked; Endogenous stem cells; In situ wound healing; Peptide scaffolds; SDF-1-mimic peptide; Wound healing; Wound healing process; Wound site; Animals; Cell Movement; Chemokine CXCL12; Hyaluronic Acid; Stem Cells; Wound Healing; Endogenous stem cell; Hyaluronic acid; In situ wound healing; Scaffold; SDF-1-mimic peptide